A Simple Methodology for Conversion of Mouse Monoclonal Antibody to Human-Mouse Chimeric Form - Vinh T. Dang; Kedar D. Mandakhalikar; Oi-Wing Ng; Yee-Joo Tan (Clinical and Developmental Immunology)
Passive immunotherapy has mainly been used as a therapy against cancer and inflammatory conditions. Recent studies have shown that monoclonal antibody-(mAb-) based passive immunotherapy is a promising approach to combat virus infection. Specific mouse mAbs can be routinely generated in large amounts with the use of hybridoma technology but these cannot be used for therapy in human beings due to their immunogenicity. Therefore, the development of chimeric and humanized mAbs is important for therapeutic purpose. This is facilitated by a variety of molecular techniques like recombinant DNA technology and the better understanding of the structure and function of antibody. The human-mouse chimeric forms allow detailed analysis of the mechanism of inhibition and the potential for therapeutic applications. Here, a step-by-step description of the conversion process will be described. The commercial availability of the reagents required in each step means that this experimentation can be easily set up in research laboratories.